Cryptoporus volvatus Extract Inhibits Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) In Vitro and In Vivo - Gao, Li; Zhang, Weiwei; Sun, Yipeng; Yang, Qian; Ren, Jie; Liu, Jinhua; Wang, Hexiang; Feng, Wen-hai (PLOS ONE, 2013)
Porcine reproductive and respiratory syndrome virus (PRRSV) is an important arterivirus that can cause significant losses in swine industry. At present, there are no adequate control strategies against PRRSV. Thus, there is an urgent need for new treatment regimens that have efficacious antiviral activity to compensate for vaccines. Cryptoporus volvatus commonly serves as an anti-infective agent in Tradational Chinese Medicines. In this report, we exploited whether the aqueous extract from the fruiting body of Cryptoporus volvatus had the potential to inhibit PRRSV infection. Our results showed that the extract significantly inhibited PRRSV infection by repressing virus entry, viral RNA expression, and possibly viral protein synthesis, cell-to-cell spread, and releasing of virus particles. However, it did not block PRRSV binding to cells. Further studies confirmed that the extract directly inhibited PRRSV RNA-dependent RNA polymerase (RdRp) activity, thus interfering with PRRSV RNA and protein synthesis. More importantly, the extract efficiently inhibited highly pathologic PRRSV (HP-PRRSV) infection in vivo, reduced virus load in serum, and increased the survival rate of pigs inoculated with HP-PRRSV strain. Collectively, our findings imply that the aqueous extract from the fruiting body of Cryptoporus volvatus has the potential to be used for anti-PRRSV therapies.